Sustainable Lies: Constructs of Greenwashing, Consumer Protection, and Interfaith Environmental Ethics in Southeast Asia - Nurlaily Nurlaily; Farahdilah Ghazali; Jonathan P. Binaluyo; Lu Sudirman; Emiliya Febriyani (Contemporary Issues on Interfaith Law and Society, 2026)
Greenwashing constitutes a spectrum of crime that exploits not only consumer trust but also the fundamental principles of environmental sustainability designed to ensure the preservation of the environment. This study analyzes the normative constructs of greenwashing and its implications, evaluating how existing legal frameworks in Indonesia, Malaysia, and the Philippines address this pervasive issue. Employing a normative legal research methodology supplemented by a comparative approach, this study deconstructs greenwashing into a spectrum of legally culpable conduct. This ranges from misleading commercial representation and administrative manipulation to criminal deception involving fraud, false reporting, the concealment of violations, and broader environmental-crime nexuses. An analysis of the relevant frameworks across the three jurisdictions reveals significant normative gaps indicative of deeper structural problems. These deficiencies include a failure to legally connect greenwashing with environmental crimes, inadequate compliance mechanisms, weak penal sanctions, and an overall failure to comprehensively cover the greenwashing spectrum. To address these gaps, this study proposes a set of actionable recommendations designed for adoption by lawmakers in Indonesia, Malaysia, and the Philippines